RESOLVING PROVINCIAL CROSS- BORDER DISPUTES UNDER THE CONSUMER PROTECTION ACT - Stephen Newman; Mark Tait (Obiter, 2018)
This research sets out a practical enforcement problem which provincial consumer protection authorities are faced with under the Consumer Protection Act 68 of 2008. In the initial period after the Act became effective, many of the provincial authorities received complaints that involved the consumer and supplier being in different provinces. In terms of section 84 of the Act, which sets out jurisdictional limits of the provincial authorities, it appears that provincial authorities were only able to intervene in a dispute where the consumer and supplier are present in their province. The provincial authorities referred such cross-border disputes to the National Consumer Commission for resolution as the Commission has jurisdiction throughout the country. The Commission refused to deal with these individual disputes. This research sets out the sections of the Act, and other measures, which could potentially be used to try to resolve this situation.